2013
DOI: 10.1016/j.jclepro.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Improved economic viability of integrated biogas energy and compost production for sustainable palm oil mill management

Abstract: This paper proposes a new approach for integrated technology of biogas energy and compost production for a palm oil mill. This study evaluated the economic viability based on the changes of materials flow and energy balance when a palm oil mill introduces this approach. A palm oil mill processing 54 tonnes fresh fruit bunch (FFB) per hour has the potential to produce 8.2 GWh per year of electricity using biogas captured during anaerobic treatment of palm oil mill effluent (POME). Compost production using shred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(30 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…Other types of co-compost can also be explored such as a mix of palm fronds with palm oil mill effluent sludge (Ahmad et al, 2011). Integrated combination of methane capture and compost production may also be a suitable option (Stichnothe and Schuchardt, 2010;Yoshizaki et al, 2013). The comparison of these different options in order to harness the best from all potential recycled materials need to account for both the benefits and risks for the palm agroecosystem and the potential net input-output gain at the whole supply chain level.…”
Section: Introductionmentioning
confidence: 99%
“…Other types of co-compost can also be explored such as a mix of palm fronds with palm oil mill effluent sludge (Ahmad et al, 2011). Integrated combination of methane capture and compost production may also be a suitable option (Stichnothe and Schuchardt, 2010;Yoshizaki et al, 2013). The comparison of these different options in order to harness the best from all potential recycled materials need to account for both the benefits and risks for the palm agroecosystem and the potential net input-output gain at the whole supply chain level.…”
Section: Introductionmentioning
confidence: 99%
“…The other major resource being wasted is excess steam produced through burning of oil palm oil biomass (Yoshizaki et al, 2013). The integration and effective utilization of biomass and excess steam are believed to provide eco-processes and green products towards a sustainable oil palm industry.…”
Section: Introductionmentioning
confidence: 99%
“…The latest research found that composting of empty fruit bunches together with palm oil mill effluent and compatible multi-enzymatic fungal system produced matured compost with C/N ratio of 17 (Mohammad et al 2013). Nevertheless, installing compost technology alone is troublesome due to the characteristics of raw palm oil mill effluent; plus composting with this effluent requires additional microbes and enzymes for maintaining product quality and water content (Yoshizaki et al 2013). Although composting of empty fruit bunches under aerobic conditions is more effective, the process requires a turning machine and intensive labor (Kananam et al 2011).…”
Section: Introductionmentioning
confidence: 99%